Peningkatan Kemampuan Guru dalam Penyusunan Kriteria Ketuntasan Minimal (KKM) melalui Workshop (Penelitian Tindakan di MTsN 2 Kota Lhokseumawe) - Nurlaila (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
In the 2013 Curriculum (Kurtilas), learning through any method or model is inseparable from the evaluation of determining the Minimum Competency Criteria (KKM) as the initial stage of assessing learning outcomes. In reality, many teachers still fail to analyze and consider the principles in determining the KKM. The aim of this research is to improve teachers' skills in developing KKM at MTsN 2 Kota Lhokseumawe. The emancipatory type was chosen as the method for this action research. The Kemmis model design was used as the research design, consisting of four stages: planning, implementation, observation, and reflection. This action research also encouraged the researcher to deeply address practical problems in educational institutions. Based on the research findings and discussions, it can be concluded that the workshop enhanced teachers' ability to develop KKM. In the first cycle, three out of five criteria for assessing teachers' performance did not meet the criteria. However, in the second cycle, all aspects met the criteria. The assessment results for determining the KKM improved; in the first cycle, the ability to determine the KKM reached 83.75%, while in the second cycle, there was an increase to 93.25%. The research findings also indicated a significant increase in the percentage of teachers ready to fulfill the workshop implementation aspect. Therefore, it can be said that the response of teachers at MTsN 2 Lhokseumawe towards the workshop activities was very positive.